A prospective study of adverse drug reactions to antiepileptic drugs in children - Anderson, Mark; Egunsola, Oluwaseun; Cherrill, Janine; Millward, Claire; Fakis, Apostolos; Choonara, Imti (BMJ Publishing Group, 2015)
Objectives To prospectively determine the nature and rate of adverse drug reactions (ADRs) in children on antiepileptic drugs (AEDs) and to prospectively evaluate the effect of AEDs on behaviour.